Redescription and phylogenetics of Allobates trilineatus (Boulenger 1884 “1883”) (Anura: Aromobatidae) based on topotypic specimens - Jaramillo, Andrés F.; Gagliardi-Urrutia, Giussepe; Simões, Pedro Ivo; Castroviejo-Fisher, Santiago (Zootaxa, 2021)
Allobates trilineatus is the second most geographically widespread species in the genus Allobates, its range extending from northern Ecuador to southern Peru along the Andean foothills of Amazonia and to the east, into Acre, Brazil. However, detailed phenotypic and genetic variation from topotypic specimens is lacking, raising doubts about the identification of specimens in the literature. To solve this problem, we collected 16 topotypic specimens—including male and female adults and juveniles—and associated data such as advertisement calls and tissue samples. Based upon this material, we redescribe the phenotypic variation within A. trilineatus and evaluate its phylogenetic position using a fragment of the mitochondrial gene 16S rDNA. Allobates trilineatus is distinguished from its congeners by its small body size (adult snout-to-vent-length = 14.6–16.6 mm), preserved males with dark gray throat, and gray chest and belly, pale dorsolateral stripe straight and conspicuous, and advertisement call formed by the emission of groups of note-pairs with dominant frequency at 5.06–5.81 kHz. Our phylogenetic results indicate that none of the specimens assigned to this species in previous phylogenetic studies cluster within the clade formed by topotypic samples, except for the sample of one tadpole. Furthermore, our comparison of published phenotypic and genetic data assigned to A. trilineatus with our new data led us to conclude that A. trilineatus as previously recognized was actually a complex of cryptic, closely related species. Although with the data at hand we cannot fully resolve the taxonomy of all sampled populations in previous studies, we provide a new definition and delimitation of A. trilineatus sensu stricto, assign other specimens to different evolutionary units corresponding to candidate species, and flag other important taxonomic issues.